Where Water Has a Will: The Cenotes in Yucatan, Mexico - Castillo Cisneros, María del Carmen (2026)
Cenotes, essential for life in Yucatan, Mexico, are not merely water resources for Maya communities, but spaces endowed with life (kuxa'an), will, agency, and affectivity—beings with whom people coexist and establish situated, reciprocal relationships. This article, drawing on an ethnographic approach, explores the relationships local populations maintain with cenotes, which, as living spaces, intertwine affective, material, and relational dimensions. Based on fieldwork in the communities of Cuzama and Homun, it examines two contemporary forms of relationship: the primarily touristic use of cenotes as natural swimming pools—that is, natural bodies of water adapted for recreation—and the local preference for artificial pools, purpose-built to contain and control water. This distinction makes it possible to study local practices of distancing from cenotes and approaching pools, as shaped by cosmopolitical rules of respect toward the nonhuman beings who inhabit them—their dueños. The article examines how these uses transform traditional bonds, in a context where the subterranean, humid, and dark is a space of both power and danger, inhabited by harmful winds that manifest themselves in various ways, including through animal forms. Finally, it addresses the ontological risk of deactivating the relationships that sustain cenotes as living beings, amid the advance of touristification. This study offers a reflection on the importance of maintaining sensitive and respectful bonds with the more-than-human local environments—relationships that have always existed and form an integral part of everyday life in indigenous communities.